The effectiveness of applying kinesiology tape base on skill related fitness among football players / Muhammad Faizal Abdul Rahim - Abdul Rahim, Muhammad Faizal (Faculty of Sport Sciences and Recreation, 2020)
The purpose of this study was to identify the effect of kinesiology tape on lower limb speed, power and agility performance among football players Peqedu FC. Twenty (N=20) players from Peqedu FC (22.15±1.49; years, 168.9±3.99; em, 67.25±7.19; kg) were participated in this study. This experiment were using three tests on football players. The subjects undergo two conditions which were pre non kinesiology tape and post apply kinesiology tape. They performed test 30 meter sprint test to measured speed, standing broad jumped to measured power and Illinois to measured agility. The group will perform all the test in one day without applying kinesiology tape and applied kinesiology tape within 24 hours prior to the post-test. Results shown that there were no significant effect of applying kinesiology tape (p<0.05) on speed, power and agility. The application of kinesiology tape on a lower limb does not have an effect on speed, power, and agility on the performance of the athlete